The Legal Hurdles in Executing Land Dispute Cases in Court - Hatta, Muhammad; Anditya, Ariesta Wibisono; Rayhan, Ahmad; Akhmaddhian, Suwari; Anugrah, Dikha (Universitas Kuningan, 2024)
The study aims to critically analyse the regulatory framework governing the execution of civil dispute cases in Indonesia and to evaluate the practical implementation of such executions within the jurisdiction of the Kuningan District Court. The study encompasses an empirical juridical method involving fieldwork that was conducted at the Kuningan District Court. The finding shows the execution of court decisions is governed by various legal provisions, such as Article 27(1) and Article 28D(1) of the 1945 Constitution of the Republic of Indonesia, Article 1365 of the Indonesian Civil Code, Article 196 of the Herzien Inlandsch Reglement (HIR) or Article 207 of the Rechtreglement voor de Buitengewesten (RBg), Article 66(2) of Law No. 3 of 2009 concerning the Second Amendment to Law No. 14 of 1985 on the Supreme Court, Articles 54(2), 54(3), and 55(1) of Law No. 48 of 2009 on Judicial Power, and Supreme Court Circular No. 1 of 2010 regarding Requests for Execution Assistance. Even though its execution process has some issues, the study finalises that the resolution of cases and the enforcement of court decisions are governed by relevant legal regulations. As the legal structures, legal substance, and legal culture put a heavy weight on it, the execution process of land dispute cases at the Kuningan District Court has not yet been optimally implemented. Accordingly, to prevent prolonged execution processes that could drain time, energy, and financial resources, the court is encouraged to adhere to the principle of legal certainty that has legal finality.